Spectroscopic Properties of the Interaction between Chlorophyll and Agrochemicals - Moreira, Leonardo Marmo; Ramos, Jane de Morais; de Oliveira, Hueder Paulo Moisés; Romani, Ana Paula (Orbital: The Electronic Journal of Chemistry, 2018)
The present work is focused on spectroscopic evaluations, employing optical absorption and fluorescence emission spectroscopies of chlorophylls and chlorophilic derivatives as well as the complex chemical systems originated by the interaction between chlorophyll compounds and agrochemicals, such as pesticides and insecticides. Considering the great variation of chlorophyll compounds that can be encountered in each plant species as well as the high number of agrochemicals that are frequently used in the agriculture, this approach can be considered a relevant contribution to understand some mechanisms of chemical interaction and toxicological risks inherent to the chlorophyll-pesticides and chorophyll-insecticides systems. This work also demonstrates that the high coefficient of molar absorptivity of chlorophyll as well as its great level of spectral details in terms of absorption bands can be employed as a model system to evaluate the intensity of contamination of plants with agrochemicals. This manuscript represents a multi- and interdisciplinary study, which is highly relevant to professionals and researchers of several distinct areas of knowledge. The results obtained are discussed in details, demonstrating that time-resolved fluorescence measurements are able to analyze the photophysical processes that involve chlorophylls, agrochemicals and the complex chemical systems formed by the interaction between chlorophylls and these compounds of high toxicity. DOI: http://dx.doi.org/10.17807/orbital.v10i6.1160